Analisis Pengaruh Non Performing Loan (NPL) Dan Struktur Modal Terhadap Profitabillitas Yang Dimediasi Oleh Pertumbuhan Kredit (Studi pada BPR di Provinsi Jawa Tengah Periode Tahun 2019-2021) - Cahyo Cahyo; Sri Harjanto; Putu Sulastri (International Forum of Researchers and Lecturers, 2023)
This study concerns profitability, aiming to analyze the effect of Non Performing Loans (NPL) and capital structure on profitability mediated by credit growth. The population of this study were all Rural Banks (BPR) in Central Java province, totaling 257 BPRs. This study used purposive sampling, with the criteria being a private BPR with its head office in Central Java province and reporting complete financial data for the 2019-2021 period. Methods of data analysis using multiple linear regression analysis and data processing using SPSS. The results of hypothesis testing show that Non-Performing Loans (NPL) have a significant negative effect on credit growth. Capital structure have a significant positive effect on credit growth. Credit growth have a positive but not significant effect on profitability. Non Performing Loans (NPL) have a significant negative effect on profitability. Capital structure have a significant positive effect on profitability. The results of the analysis of mediating variables using the Sobel test, found that credit growth cannot mediate the effect Non Performing Loans (NPL) against profitability.Credit growth cannot mediate the effectcapital structure on profitability.